Die Übersetzung juristischer Fachbegriffe im Roman Der Fall Collini Ferdinand von Schirachs - Filipović, Ana; Lovrić, Goran (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
This article focuses on legal translation, one of the most complex areas of translation, as it requires both sound linguistic and extensive subject- matter expertise. The translation of legal terms is analyzed using the example of the translation of Ferdinand von Schirach’s novel Der Fall Collini into the Croatian language as Slučaj Collini. Since the novel contains a multitude of legal terms and was written by an author who is lawyer himself, it provides a rich basis for the analysis of legal terminology. Specialized translation in the field of legal language requires not only comprehensive knowledge of the source and target languages, but also of the respective legal systems. This paper investigates the translation of legal terms in the novel through a detailed analysis, aiming to demonstrate which translation methods with an emphasis on functional and denotative equivalence are best suited to adequately conveying the function, designation, and meaning of complex legal concepts.